Microalbuminuria in Children: A Comparative Study of HIV-Infected and Non-Infected Children in Jos, Nigeria - M Ihekaike, Marcia; E Ocheke, Isaac; Oguche, Stephen (Journal of Pediatric Nephrology, 2021)
Background and Aim: Kidney disease occurs frequently in human immunodeficiency virus (HIV) infected individuals and is a leading contributor to morbidity and mortality in patients with HIV. Early detection of kidney damage will aid in instituting interventional measures that could slow down or halt the progression of kidney disease. The aim of this study was to determine the prevalence and risk factors of microalbuminuria in HIV infected children in Jos, Nigeria and compare them with those of HIV negative children. Methods: A total of 135 HIV infected and 135 HIV uninfected children aged 1-18 years were screened for microalbuminuria using microalbumin 2-1 combo test strips. Logistic regression analysis was used for determination of the association between microalbuminuria and various predicted risk factors. Results: Thirty (22.2%) HIV infected and 13 (9.6%) uninfected children had microalbuminuria (p = 0.001). Logistic regression analysis showed that an increase in the WHO clinical stage was significantly associated with the presence of microalbuminuria in HIV infected children (p = 0.004). Conclusion: The prevalence of microalbuminuria is higher in HIV infected children, as such the detection of microalbuminuria as early as possible in the course of the disease and prompt initiation of therapy are very important in our resource poor environment.